7x-2x+9+3x+8-5x+6=5

Simple and best practice solution for 7x-2x+9+3x+8-5x+6=5 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 7x-2x+9+3x+8-5x+6=5 equation:


Simplifying
7x + -2x + 9 + 3x + 8 + -5x + 6 = 5

Reorder the terms:
9 + 8 + 6 + 7x + -2x + 3x + -5x = 5

Combine like terms: 9 + 8 = 17
17 + 6 + 7x + -2x + 3x + -5x = 5

Combine like terms: 17 + 6 = 23
23 + 7x + -2x + 3x + -5x = 5

Combine like terms: 7x + -2x = 5x
23 + 5x + 3x + -5x = 5

Combine like terms: 5x + 3x = 8x
23 + 8x + -5x = 5

Combine like terms: 8x + -5x = 3x
23 + 3x = 5

Solving
23 + 3x = 5

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-23' to each side of the equation.
23 + -23 + 3x = 5 + -23

Combine like terms: 23 + -23 = 0
0 + 3x = 5 + -23
3x = 5 + -23

Combine like terms: 5 + -23 = -18
3x = -18

Divide each side by '3'.
x = -6

Simplifying
x = -6

See similar equations:

| x-3(x-12)=26 | | 5(3x+2)=32.5 | | (x-3)(15-6x)=0 | | 17=2x+8 | | x(2x-5)=8 | | 15x-40+21x+18=48x+18-8x-20 | | ax+2=3x+a | | 4x+4=4y | | 12w^4+56w^3+32w^2=0 | | x^4=-25 | | 5x+13=42 | | 4y+10=46 | | 4u^3w^4+12u^9w^6x^9=0 | | 8.7+3.6-5.3= | | 12-10x=80-38x | | 3(4x+5)(3x-2)=0 | | 6(n+4)=8+7n | | 18d-4d-6d-8=2d | | -5m=4m+8 | | 7(m-3)=4(m+3) | | (2x-6)m=26 | | 4(z+2)-2z=10+3(z-3) | | 2(x+7)=40 | | -3.5(4a+1.9)a= | | -3.5(4a+1.9)= | | 4(x-8)=80 | | 8x^2+8x^6= | | (2x+3)(2-3x)-(2-3x)(4x+1)=0 | | y=3x+5y | | xy=3x+5y | | 32v^4-2u^4v^4=0 | | 3(w+3)=2w-2 |

Equations solver categories